2022
DOI: 10.4081/ripppo.2022.609
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and mental health: A web-based survey among the Italian population dealing with COVID-19

Abstract: Coronavirus disease (COVID-19) continues to be a highly stressful event with a major impact on psychological mental health worldwide. The use of different coping strategies may change the perception of psychological well-being during the pandemic. The present study aims to explore psychological mental health in relation to sociodemographic variables and to analyze the coping strategies of the Italian population in dealing with COVID-19. Implications for clinical interventions are reported. A total of 537 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…A large body of literature has demonstrated that psychological difficulties have risen significantly during the government-imposed lockdown during the COVID-19 pandemic (Shah et al , 2021 ). The resulting physical and social isolation has been shown to affect people’s mental health (Knight, 2020 ; O’Donnell et al , 2022 ; Rossi et al , 2022 ), thus increasing the risk of developing mental disorders (Fancourt et al ., 2021 ; Ierardi et al, 2023 ; Varma et al ., 2021 ). Consequently, investing in improving overall well-being is more important than ever before (Békés et al ., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature has demonstrated that psychological difficulties have risen significantly during the government-imposed lockdown during the COVID-19 pandemic (Shah et al , 2021 ). The resulting physical and social isolation has been shown to affect people’s mental health (Knight, 2020 ; O’Donnell et al , 2022 ; Rossi et al , 2022 ), thus increasing the risk of developing mental disorders (Fancourt et al ., 2021 ; Ierardi et al, 2023 ; Varma et al ., 2021 ). Consequently, investing in improving overall well-being is more important than ever before (Békés et al ., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that positive coping strategies, which allow individuals to reinterpret negative situations, were positively correlated with psychological well-being during the COVID-19 pandemic. In contrast, avoidance strategies, characterized by refusing to deal with problems, negatively influenced well-being during the pandemic (Rossi et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This technique facilitates the identification of patterns and relationships within datasets that feature numerous variables and participants with similar underlying traits. In research applications, identifying distinct personality profiles sheds light on the interplay between specific traits and their impact on probability of adjustment/maladjustment [31,32].…”
Section: Introductionmentioning
confidence: 99%